A practical guide to biomedical research : for the aspiring scientist - Agger, Peter; Stephenson, Robert S.; Hasenkam, J. Michael (Springer, 2017)
This book advises and supports novice researchers in taking their first steps into the world of scientific research. Through practical tips and tricks presented in a clear, concise and step-wise manner, the book describes the entire research process from idea to publication. It also gives the reader insight into the vast opportunities a research career can provide. The books target demographic is aspiring researchers within the biomedical professions, be it medical students, young doctors, nurses, engineers, physiotherapists etc. The book will help aspirational inexperienced researchers turn their intentions into actions, providing crucial guidance for successful entry into the field of biomedical research.
Includes index.
Keywords: Biology -- Research -- Handbooks, manuals, etc.; elektronické knihy; electronic books